Inovasi Solar Dryer Dome pada Usaha Budidaya Multiguna untuk Mendukung Urban Farming di Ekowisata Sungkai Green Park Lambung Bukit Pauh Kota Padang - Daud, Darwison; Zaini; Rusydi, M Ilhamdi; Aulia; Novizon; Yunus, syukri; Novendra, Rico; Muharam, Mumuh; Novandri, Athalla; Mubarok, Fatih; Susanti, Roza (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2024)
The implementation of the Solar Dryer Dome innovation in Sungkai Green Park Ecotourism, Lambung Bukit Village, Pauh District, Padang City, is a strategic step in supporting urban farming practices. Lecturers and students from the Department of Electrical Engineering, Faculty of Engineering, Andalas University, have successfully integrated this technology in the cultivation of vegetables, fish, broiler chickens, and the tea drying process. This infrastructure is equipped with a UV plastic roof to protect plants from excessive UV rays, while the center of the dome functions as a fish pond that utilizes fish waste as natural fertilizer for plants. The IoT-based control system allows efficient monitoring and control via mobile devices, with various sensors for temperature, humidity, soil pH, and water quality. As a result, harvest time becomes more efficient—vegetables in 21-27 days, gourami fish around 1000 per year, broiler chickens in 30 days, and dried tea in 8 hours in sunny weather. The specific objectives of implementing this innovation at the Solar Dryer Dome location are to increase production efficiency, reduce operational costs, and improve product quality, all of which have a positive impact on local food security. This initiative also supports sustainable urban farming practices and improves community knowledge and skills in modern agriculture. Overall, the Solar Dryer Dome has a significant positive impact on the community and the surrounding environment.